Inter-art Relationship in Sujan Chitrakar’s Artworks - Sharma, Yam Prasad (International Research Journal of MMC, 2022)
Sujan Chitrakar’s visual arts present inter-art relationship among various art genres like photography, painting, literature and sculpture. Within a single artwork, there are the elements of two or more art genres. Chitrakar uses photographs as references and integrates them in canvas in the renewed form. Some of his works present poem and painting in the same canvas. Both verbal and visual arts are integrated in the same artwork. Similarly, three dimensional objects are installed on the two dimensional surface of the canvas. Three dimensions are the special characteristics of sculpture whereas painting has only two dimensions. Chitrakar’s creative impulse breaks the boundaries of conventional art genres. His artworks provide social and political commentary responding to the contemporary context.